2013
DOI: 10.1371/journal.pone.0055804
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Care in a Nursing Home in Italy

Abstract: IntroductionMalnutrition is a clinical condition due to the imbalance among needs, intake and use of nutrients, leading to the increase of morbidity and mortality, and to the impairment of quality of life. Even in industrialized countries undernutrition is becoming an alarming phenomenon, especially involving elderly institutionalized subjects.A multicentric study called PIMAI (Project Iatrogenic MAlnutrition in Italy), was carried out in Italy over 2005. The aims of this study were to determine the prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 48 publications
6
15
0
6
Order By: Relevance
“…In this cross-sectional study, most of the participants were females (70.2%) and they were older than the males, which is similar to most studies carried out in elderly nursing home residents (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Weight was higher in males but BMI was higher in females, in part due to their lower height (which could be influenced by the higher age and the higher prevalence of osteoporosis in females).…”
Section: Discussionsupporting
confidence: 77%
“…In this cross-sectional study, most of the participants were females (70.2%) and they were older than the males, which is similar to most studies carried out in elderly nursing home residents (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Weight was higher in males but BMI was higher in females, in part due to their lower height (which could be influenced by the higher age and the higher prevalence of osteoporosis in females).…”
Section: Discussionsupporting
confidence: 77%
“…This disorder does not appear to be associated with increased comorbidity and/or use of drugs. Previous studies have shown an inverse correlation between cognitive impairment and comorbidity in a large sample of patients admitted to nursing homes:34,35 it was found that the prevalence of defined cardiovascular diseases, such as hypertension, decreased in relation to increased dementia severity,36 although other authors disagree: the comorbidity is inversely correlated with the degree of cognitive impairment 37. Moreover, some studies have shown a relationship between nutritional state and comorbidities 38.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly individuals with dementia frequently have difficulty feeding themselves and may not understand the importance of maintaining good nutritional status (Cole, 2012). The nutritional status of geriatric populations is an issue that deserves greater attention from healthcare providers and caregivers (Donini, Neri, De Chiara, Poggiogalle, & Muscaritoli, 2013;Saka, Kaya, Ozturk, Erten, & Karan, 2012).…”
Section: Introductionmentioning
confidence: 99%